1998
DOI: 10.1046/j.1365-2370.1998.00109.x
|View full text |Cite
|
Sign up to set email alerts
|

Strong association between DQA1/DQB1 genotype and early‐onset IDDM in Chinese: the association is with alleles rather than specific residues

Abstract: We report on the role of HLA-DQA1 and DQB1 alleles in determining susceptibility to insulin-dependent diabetes mellitus (IDDM) in Hong Kong Chinese and investigate whether these alleles affect the age of onset of the disease. We studied 76 unrelated Chinese patients and 250 controls. There was no apparent predisposing effect of non-aspartic acid residues at position 57 of the DQ beta chain (Asp57-) but there was an excess of homozygous genotypes containing arginine at position 52 of the DQ alpha chain (Arg52+)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…DR4/DQ8 haplotype occurs more frequently in early-onset patients than in later-onset patients (25). The frequency of the DQA1/*0301/ DQA1*0501 haplotype has been reported to be higher in Chinese patients with type I diabetes with early disease onset than in patients with later disease onset (26). Also, the frequencies of DR3 and DR3/DR4 haplotypes were increased inversely with the age at onset (27).…”
Section: Discussionmentioning
confidence: 97%
“…DR4/DQ8 haplotype occurs more frequently in early-onset patients than in later-onset patients (25). The frequency of the DQA1/*0301/ DQA1*0501 haplotype has been reported to be higher in Chinese patients with type I diabetes with early disease onset than in patients with later disease onset (26). Also, the frequencies of DR3 and DR3/DR4 haplotypes were increased inversely with the age at onset (27).…”
Section: Discussionmentioning
confidence: 97%
“…Thus T cell selection is a complex system of antagonizing mechanisms equilibrating immune defenses against self-and foreign antigens. In this regard, for instance A24-restricted T cells may be involved in β-cell destruction supported by mechanisms acting in the selec-HLA Class I genes and autoimmune diabetes Results obtained from genetic studies conducted in the fashion of patients vs. controls have demonstrated that HLA class II genes are clearly associated with the occurrence of high levels of autoantibodies against antigens, such as the 65 kDa isoform of GAD, GAD65 [29], and that these genes contribute decisively to the onset of autoimmunity [7,9,13]. The role of class I genes in the early stages of the disease is disputed.…”
Section: Functional Impact Of Hla Class I Genes and Molecules On The mentioning
confidence: 99%
“…Early age of onset (≤ 10 yr) is genetically associated with highly susceptible HLA class II alleles from DQA1, DQB1 and DR3 subgroups e.g. the DQA1*0301/DQA1*05011 genotype and the DQA1*0302 allele in a Chinese [7,8], the DQB1*02/*0302 genotype in a Finnish [9] and the DR3 serotype and A30-B18-DR3 haplotype in a Caucasian population [10]) as well as A*2402 [11]. In contrast, later age of onset (≥ 15 yr) carries haplotypes, which also include protective alleles [9,[12][13][14].…”
mentioning
confidence: 99%
“…The 12 th International Histocompatibility Workshop Study reported increased frequencies of DRB1*03 and DRB1*04 in all populations studied [11]. High resolution analysis revealed that although DRB1*0401,*0402,*0405, and heterozygote *0301/*0401 were the predominant alleles associated with susceptibility to type 1 diabetes in most of the Caucasian [11,12] and Black populations [13], these are replaced by DRB1*0301/0901 in Chinese [14] and Koreans [15], whereas DRB1*0802/ *0405 predominates amongst the Japanese [12]. On the other hand, HLA-DRB1*15, *0403, *0404, and *0407 have been reported to confer protection against the development of type 1 diabetes in most ethnic groups [11].…”
Section: Introductionmentioning
confidence: 99%